Youth participation: Adultism, human rights and professional youth work - Corney, Tim; Cooper, Trudi; Shier, Harry; Williamson, Howard (Children & society, 2022)
This article argues that the right of young people to participate in decisions being made about them forms the basis for professional youth work practice. The authors consider the nature of ‘participation’ and its relation to human rights, and introduces the concept of ‘adultism’ and the challenges for youth workers combatting ‘adultist’ beliefs and practices in the work of participation. The paper considers the benefits and limitations of youth participation models, and addresses the relationship between rights‐based participation practice, and critical pedagogy (dialogical) in youth work.